Cessation of E-Cigarette Use Among Adolescents and Its Associated Factors. (October 2019) - Saminathan, Thamil Arasu; Rodzlan Hasani, Wan Shakira; Robert Lourdes, Tania Gayle; Mohd Yusoff, Muhammad Fadhli; Ismail, Hasimah; Akmal Abd Hamid, Hamizatul; Mat Rifin, Halizah; Ling, Jane Miaw Yn; Ab Majid, Nur Liana; Ahmad, Azhairin
We assessed the prevalence of cessation of e-cigarette and its associated factors among adolescents in Malaysia. This study analyzed data from the Tobacco and E-Cigarette Survey among Malaysian Adolescent (TECMA) in 2016, a cross-sectional study with 2-stage stratification cluster sampling. A total of 14 832 school-going adolescents aged 10 to 19 years participated in this survey. A complex sampling design and multiple logistic regression analysis were applied. Nearly half of the adolescents (49.9%; 95% confidence interval [CI] = 44.9-55.0) who had ever used e-cigarette ceased the usage. Based on multivariate analysis, adolescents were more likely to quit e-cigarette because they could not afford the e-cigarette (adjusted odds ratio [aOR] = 2.39, 95% CI = 1.78-3.20), if they are aged 13 year and older (aOR = 1.80, 95% CI = 1.25-2.61), and those who claimed their e-cigarette does not contain nicotine (aOR = 1.35, 95% CI = 1.03-1.78). E-cigarette prevention efforts among adolescents could consider the cessation factors described in this study.